1985
DOI: 10.1210/jcem-61-4-672
|View full text |Cite
|
Sign up to set email alerts
|

Serum Ferritin as a Marker of Thyroid Hormone Action on Peripheral Tissues*

Abstract: Serum ferritin measurements were evaluated as a marker of thyroid hormone action on peripheral tissues. Mean serum ferritin concentrations were not significantly different in euthyroid, thyrotoxic, and hypothyroid subjects due to a wide spread in ferritin levels among individuals. Intraindividual changes in serum ferritin, however, occurred with changing thyroid function. All 18 patients with thyrotoxic Graves' disease had a decrease in serum ferritin levels when they became euthyroid during antithyroid drug t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
3

Year Published

1989
1989
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 10 publications
1
25
0
3
Order By: Relevance
“…Several groups have reported that T 3 positively regulates serum ferritin in humans (Macaron & Macaron 1982, Van de Vyver et al 1982, Takamatsu et al 1985, Hashimoto & Matsubara 1989, Kubota et al 1993, Barnum-Huckins & Adrian 2000. Elevated serum ferritin levels were observed in hyperthyroid individuals, and levels decreased significantly after antithyroid treatment which helped to normalize T 3 levels (Macaron & Macaron 1982, Van de Vyver et al 1982, Takamatsu et al 1985, Kubota et al 1993, Barnum-Huckins & Adrian 2000.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups have reported that T 3 positively regulates serum ferritin in humans (Macaron & Macaron 1982, Van de Vyver et al 1982, Takamatsu et al 1985, Hashimoto & Matsubara 1989, Kubota et al 1993, Barnum-Huckins & Adrian 2000. Elevated serum ferritin levels were observed in hyperthyroid individuals, and levels decreased significantly after antithyroid treatment which helped to normalize T 3 levels (Macaron & Macaron 1982, Van de Vyver et al 1982, Takamatsu et al 1985, Kubota et al 1993, Barnum-Huckins & Adrian 2000.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated serum ferritin levels were observed in hyperthyroid individuals, and levels decreased significantly after antithyroid treatment which helped to normalize T 3 levels (Macaron & Macaron 1982, Van de Vyver et al 1982, Takamatsu et al 1985, Kubota et al 1993, Barnum-Huckins & Adrian 2000. Furthermore, administration of T 3 to hypothyroid individuals produced a significant increase in the serum ferritin level (Takamatsu et al 1985, Hashimoto & Matsubara 1989. Leedman et al (1996) reported that T 3 regulates the Iron response element (IRE) binding activity of the IRP.…”
Section: Discussionmentioning
confidence: 99%
“…The patient was a 13-year-old Japanese girl, previously reported by us (Patient A in [7]). Briefly, she was initially diagnosed as having generalized resistance to TH at the age of 11.…”
Section: Subject and Methodsmentioning
confidence: 86%
“…Furthermore, BMR values were unchanged and no aggravation of thyrotoxicosis took place during 1-T3 administration. Takamatsu et al (1985) reported that serum ferritin level was increased by short term administration of 1-T3 and its response to thyroid hormone is useful in the diagnosis of thyroid hormone resistance. Moreover, Graninger et al (1986) reported that endoreticulum related protein such as fibronectin, ACE, factor VIII related antigen and tissue plasminogen activator were increased by 1-T3 administration in normal subjects.…”
Section: Discussionmentioning
confidence: 99%